Membangun Desa Mandiri Pupuk Berbasis Zero Waste Sebagai Upaya Peningkatan Taraf Hidup Masyarakat Kecamatan Anggrek Kabupaten Gorontalo Utara - Syamsul Bahri; Nurmi Nurmi (Univeristas Negeri Gorontalo, 2022)
The increased production of agriculture to meet food needs faces a major challenge in developing environmentally-friendly fertilizer. This activity is aimed at educating crop cultivation and training in the technology of crop growing (organic fertilizers), assisting covid-19 disease prevention programs and helping undergrowth programs primarily related to the scientific discipline of each project student in the